Discrete Polymetallic Arrangements of AgI and CuI Ions Based on Multiple Bridging Phosphane Ligands and π–π Interactions1. Issue 18 (27th May 2015) - Attenberger, Bianca; El Sayed Moussa, Mehdi; Brietzke, Thomas; Vreshch, Volodimir; Holdt, Hans‐Jürgen; Lescop, Christophe; Scheer, Manfred
Abstract: A simple and straightforward approach to new polymetallic Ag I and Cu I supramolecules is presented. The reaction of N, P, N, P, N ligand2 with Ag I ions affords a trimetallic complex bearing a triangular Ag3 core; metallophilic interactions are stabilized by ligands that display a multiple bridging coordination mode as 10‐electron donors. Heteroleptic polymetallic Ag I and Cu I complexes based on ligand2 and the 1, 12‐diazaperylene (dape) ligand are obtained by an alternative molecular organization of the polymetallic arrays compared to that in homoleptic complexes of ligand2 . Abstract : Reaction of an N, P, N, P, N ligand with Ag I ions affords a stereoselective Ag3 triangular macrocyclic complex composed of multiple bridging phosphane ligands acting as unprecedented 10‐electron donors. N, P, N, P, N and N, N 1, 12‐diazaperylene (dape) ligands with Ag I or Cu I ions lead to Ag3 and Cu5 heteroleptic columnar complexes revealing polymetallic linear structures with extended π–π interactions.